Penguatan Ketahanan Nasional melalui Program Makan Bergizi Gratis di Indonesia: A Systematic Literature Review: Strengthening National Resilience through the Free Nutritious Meal Program in Indonesia a Systematic Literature Review - Mentari Dian Melvin Hulu; Maria Sukawati; Chai Bu Sen; Zian Fachrian (Jurnal Bisnis dan Ekonomi, 2026)
The Nutritious Food Program for the Community is one of the government’s strategic policies aimed at improving the nutritional status of the population while strengthening Indonesia’s national resilience. This program is not only focused on meeting nutritional needs but also has broad implications for human resource development, food security, and socioeconomic stability. Objective : This study aims to analyze the contribution of the Nutritious Food Program to strengthening national resilience through a Systematic Literature Review (SLR) approach. Methods : The research method followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data were analyzed from 16 scientific articles that met the inclusion criteria for the 2017–2025 period, obtained from national and international journals as well as reports from official institutions.   Research Results : The Nutritious Food Program has had a significant impact on improving nutritional status, reducing stunting, enhancing academic performance, and strengthening food security through the use of local foods and the strengthening of supply chains. In addition, this program also contributes to strengthening the local economy through the involvement of farmers, fishermen, and MSMEs. This study concludes that the Nutritious Food Program is a strategic instrument in supporting national resilience based on sustainable human capital development.